The pluralistic impact of artificial intelligence on theology - Oviedo Torró, Lluís (Razón y fe, 2024)
The strong development of artificial intelligence, with its numerous applications, has surprised many social sectors, including the religious sector, and it seems that theology should take note and respond to the possible challenges that arise. To do this, a first mission is to try to understand the terms of the problem or the challenges that arise, in order to be able to respond and adapt the Christian message in this new context, which requires a continuous exercise of inculturation or adaptation of Christian faith to new environments. The article sets out to review the most urgent issues on which theology is called to act, i.e. the questions that can be the subject of theological elaboration. In this sense, it is appropriate to go beyond ethical questions to focus the debate on anthropological and soteriological issues. In particular, theology is in a position to address in a special way the so-called “problem of alignment”, which for many is the big question that arises with the surprising progress of AI.